2020
DOI: 10.1101/2020.07.15.203141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Definition and Signatures of Lung Fibroblast Populations in Development and Fibrosis in Mice and Men

Abstract: The heterogeneity of fibroblasts in the murine and human lung during homeostasis and disease is increasingly recognized. It remains unclear if the different phenotypes identified to date are characteristic of unique subpopulations with unique progenitors or whether they arise by a process of differentiation from common precursors. Our understanding of this ubiquitous cell type is limited by an absence of well validated, specific, markers with which to identify each cell type and a clear consensus on the distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 70 publications
3
30
0
Order By: Relevance
“…Several human pulmonary fibroblast cell lines are already available. However, in contrast to the cell line presented here, none of the currently available human cell lines has been characterized in detail with regards to the representation of a specific mesenchymal cell sub-population ( Adams et al, 2019 ; Reyfman et al, 2019 ; Valenzi et al, 2019 ; Habermann et al, 2020 ; Liu et al, 2020 ; Travaglini et al, 2020 ). This might not only affect cellular responses to pro-fibrotic mechanical and chemical cues, but also affect epithelial-mesenchymal crosstalk and fibrotic remodeling when used in complex co-culture in vitro models (e.g., lung-on-a-chip).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several human pulmonary fibroblast cell lines are already available. However, in contrast to the cell line presented here, none of the currently available human cell lines has been characterized in detail with regards to the representation of a specific mesenchymal cell sub-population ( Adams et al, 2019 ; Reyfman et al, 2019 ; Valenzi et al, 2019 ; Habermann et al, 2020 ; Liu et al, 2020 ; Travaglini et al, 2020 ). This might not only affect cellular responses to pro-fibrotic mechanical and chemical cues, but also affect epithelial-mesenchymal crosstalk and fibrotic remodeling when used in complex co-culture in vitro models (e.g., lung-on-a-chip).…”
Section: Discussionmentioning
confidence: 99%
“…The human lung contains structural and cellular differences to the rodent lung, however, the alveolus is one of the most conserved regions between rodents and human lungs and whether the mesenchymal and epithelial cells believed to be central to development of IPF are different is still a matter of debate. Even lipofibroblasts, a cell that’s presence has been found in rodents but has long been controversial in the human lung ( Tahedl et al, 2014 ), has recently been identified in human lung ( Liu et al, 2020 ; Travaglini et al, 2020 ). Therefore, we believe that the cell line reported here provides a valuable tool for fibrosis research, offering the opportunity to investigate molecular and cellular responses of a representative mesenchymal cell to mechanical and/or chemical stimuli with high resolution and in high throughput formats.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, mesenchymal cells were mainly divided into fibroblasts, smooth muscle cells (SMCs) and pericytes, a derivative of fibroblasts with myofibroblast characteristics, that is closely associated with capillaries ( 39 ). Recent studies, including scRNAseq efforts, have vastly increased the heterogeneity of mesenchymal cells found in the human lung ( 12 15 , 20 , 22 , 26 , 27 ).…”
Section: Diversity Of Lung Cell Types and Regulatory Mechanisms Durinmentioning
confidence: 99%
“…This was increased in IPF. These authors also found that all mesenchymal subtypes contributed to the excessive ECM production in fibrosis and that there is little evidence for trans-differentiation of fibroblast subtypes and that fibroblast fate is determined early in lung development ( 15 ). This is supported by another recent study that suggested a continuous trajectory toward IPF archetypes co-occurring within fibroblasts and myofibroblasts, but not necessarily across them.…”
Section: Diversity Of Lung Cell Types and Regulatory Mechanisms Durinmentioning
confidence: 99%
See 1 more Smart Citation